2000
DOI: 10.1111/0008-4085.00013
|View full text |Cite
|
Sign up to set email alerts
|

CEO pay, firm size, and corporate performance: evidence from Canada

Abstract: Executive compensation of 755 Canadian firms is examined over the period 1991-95, and evidence is obtained consistent with previous studies: CEO pay rises with firm size and compensation is tied to company performance. In addition, executives in utilities earn lower pay, and their compensation is less responsive to performance, than is true for their counterparts in other industries. Some novel findings are also documented. First, the sales elasticity of CEO compensation is greater in larger firms. Second, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
111
1
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(143 citation statements)
references
References 20 publications
22
111
1
7
Order By: Relevance
“…Our 0.284 estimate (Table 7) is well within the range of estimates reported: 0.22 for UK and 0.41 for U.S. firms (Conyon and Murphy's 2000); 0.37 for the top 1,000 U.S. corporations (Gabaix and Landier 2008); 0.32 for U.S. banks (Barro and Barro's 1990); 0.25 for Canadian publicly traded firms (Zhou 2000); and 0.25 for small U.S. firms (total assets up to 150 million 1993 U.S. dollars) in Cyert et al (2002). This range is fairly narrow, considering differences in samples with respect to time, country, and industry, but our result fits neatly within it.…”
Section: Our Results and Other Studiessupporting
confidence: 82%
“…Our 0.284 estimate (Table 7) is well within the range of estimates reported: 0.22 for UK and 0.41 for U.S. firms (Conyon and Murphy's 2000); 0.37 for the top 1,000 U.S. corporations (Gabaix and Landier 2008); 0.32 for U.S. banks (Barro and Barro's 1990); 0.25 for Canadian publicly traded firms (Zhou 2000); and 0.25 for small U.S. firms (total assets up to 150 million 1993 U.S. dollars) in Cyert et al (2002). This range is fairly narrow, considering differences in samples with respect to time, country, and industry, but our result fits neatly within it.…”
Section: Our Results and Other Studiessupporting
confidence: 82%
“…Many studies rely on surveys of compensation consultants, such as Tower Perrin's Worldwide Total Remuneration Reports, to reach this conclusion (Abowd and Boggano, 1995;Abowd and Kaplan, 1999;Murphy, 1999;Thomas, 2009). Using actual corporate disclosures, Zhou (2000) con…rms that in , Canadian CEOs received less than half the pay of U.S. CEOs, a smaller fraction of pay in equity, and had lower wealth-performance sensitivities. Using Japanese tax records from 2004, Nakazato, Ramseyer, andRasmusen (2011) show that, controlling for …rm size, Japanese executives earned only 20% of the pay of their U.S. counterparts.…”
Section: International Evidencementioning
confidence: 99%
“…Several previous papers have indicated that a firm's total assets (TA) can be taken as a proxy for firm size (Berger and Ofek, 1995;Zhou, 2003;Zimmerman, 1983). Therefore, this paper uses two proxies, namely stock index returns for firm performance, and trade market value of total assets (TA) for firm size (see Section 3 for further details) to explore the size effects on volatility spillovers between exchange rates and tourism firm performance.…”
Section: Proxy Variables For Firm Size and Firm Performancementioning
confidence: 99%